A critical review of Korea's long-term contract for renewable energy auctions: The relationship between the import price of liquefied natural gas and system marginal price. (December 2020) - Moon, Jongwoo; Jung, Tae Yong
Abstract: The aim of Korea's Renewable Portfolio Standard (RPS) and newly adopted auction system with a long-term fixed-price renewable contract was to support renewable energy providers in hedging electricity and Renewable Energy Certificate (REC) price risks. This study found a long-run positive relationship between the import price of Liquefied Natural Gas (LNG) and System Marginal Price (SMP) in Korea, demonstrating that the fluctuations in global fuel prices are likely to increase uncertainties in renewable investments. The fixed-price contract, which cannot be revised once determined, encourages renewable energy providers' speculative decision-making, and the uncertainty caused by the contract system may discourage investment decision-making. Highlights: Examining the long-run relationship between electricity and natural gas prices. Identifying issues in Korea's renewable and auction contract policies. Discussing how the relationship affects renewable energy providers' remuneration. Criticizing the structure of the long-term fixed-price contract scheme and RPS.